Pengaruh Return On Asset, Debt To Asset Ratio, Net Profit Margin Terhadap Pertumbuhan Laba Pada PT Telkom Indonesia Tbk Periode 2015-2024 - Ary Nur Rohmah; Anum Nuryani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of Return On Assets (ROA), Leverage, Profit Margin on Profit Growth at PT Telkom Indonesia Tbk. The method in this study is quantitative. Data analysis methods used in this study include: Descriptive Statistical Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Autocorrelation Test, and Heteroscedasticity Test), Multiple Linear Regression Test, Hypothesis Test (t Test (Partial) and F Test (Simultaneous)), and Determination Coefficient Test. The results of this study indicate that the Return On Assets (ROA) variable partially does not have a significant effect on Profit Growth because the calculated t value is -0.770 < t table 2.048 and the sig value is 0.470 > 0.05. Debt To Asset Ratio (DAR) variable partially has no significant effect on Profit Growth because the calculated t value is 0.160> t table 2.048 and the sig value is 0.878 <0.05. Net Profit Margin (NPM) variable has a significant effect on Profit Growth because the calculated t value is 2.802> t table 2.048 and the sig value is 0.031 <0.05. Simultaneously Return on Asset (ROA), Debt to Asset Ratio (DAR), and Net Profit Margin (NPM) have a significant effect on the dependent variable, namely Profit Growth because the calculated F value is 5.169> F table 4.76 with a significance level of 0.042 <0.05 Keywords: Return On Asset, Debt To Asset Ratio, Net Profit Margin, Pertumbuhan Laba